Outcome of Closed Reduction and Percutaneous Cross K-Wire Fixation of Supracondylar Fractures of Humerus in Children - Mohammed, Khandaker Haris; Rahman, Md Asjadur; Pervin, Amina; Ahmed, Nadim; Hossain, Mohammad Forhad (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Supracondylar fractures of humerus are common skeletal injuries in paediatric age group in between 50-70% of elbow injuries. They are often associated with complications and are very notorious for neurovascular injuries between 5 to 9 years of age. Objective: To evaluate the outcome of supracondylar fracture of humerus with closed reduction and percutaneous cross k-wires fixation. Materials and method: A prospective study of 30 patients of Gartland type III fractures admitted in the orthopaedics department of 250 Bedded General Hospital, Tangail from January 2021 to December 2021. Results: Regarding FLYNN CRITERIA, there were 24 excellent, 3 good,2 fair, and 1 poor results. Fair and poor results were due to poor compliance to follow-up and postoperative rehabilitation. There were 4 cases with pin tract infection, 1 with elbow stiffness, and 1 with cubitus varus. Conclusion: Closed reduction and percutaneous cross k-wire fixation is a very effective and minimally invasive way of treatment of displaced supracondylar fractures of humerus. Crossed K-wire biomechanically better way of the stability of fracture reduction J Shaheed Suhrawardy Med Coll 2022; 14(1): 16-19